Development of Economical Environmental of Protection Mechanism - Rutkauskas, Aleksandras Vytautas (Ekonomika, 1998)
Economic and ecological systems are physically connected through the materials and energy metabolism: raw materials, energy resources from the ecosystem get into the economic system and then from this system go back to the ecosystem as produced goods, heat, waste and pollutant emissions. This is due to the physical law of matter conservation: the same amount of materials being used as raw materials come back in the form of production and waste. However the economic system depends not only on the natural resources, considering as raw materials for production and consumption, but on the services provided by ecosystems. too. So, it is necessary to determine and evaluate not only the role of the ecological system as the main source of inputs into the production of goods, but also to treat it as the source of neverending services enabling protection the in area of human beings and to ensure development of the ecosystem itself. No efficient use of resources may have catastrophical consequences for the future of countries in transition to market economy, including Lithuania.The main purpose of this study is to project fiscal flows (of course these flows have a contrary direction of movement) adequate to the materials flow between ecological and economic systems and to create mechanism able to ensure creation of appropriate fiscal flows and they purposeful movement. This is the basic feature of equivalent interaction between the economic and ecological systems and the main precondition of ecologically and economically sustainable development.The category economical pollution damage is used like the main instrument for disclosure of interaction between economy and ecological systems. The conception o economical environmental protection mechanism is based on the system of interests of ecological resources users to minimize their individual ecological cost and interests of ecological damage recipients - to receive an adequate compensation. The practical calculations of economical pollution damage carried out on the Lithuanian data re presented in the paper.